2019
DOI: 10.1007/s12298-019-00727-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arbuscular mycorrhizal fungi (AMF) on gene expression of some cell wall and membrane elements of wheat (Triticum aestivum L.) under water deficit using transcriptome analysis

Abstract: Mycorrhizal symbiotic relationship is one of the most common collaborations between plant roots and the arbuscular mycorrhizal fungi (AMF). The first barrier for establishing this symbiosis is plant cell wall which strongly provides protection against biotic and abiotic stresses. The aim of this study was to investigate the gene expression changes in cell wall of wheat root cv. Chamran after inoculation with AMF, Funneliformis mosseae under two different irrigation regimes. To carry out this investigation, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…AMF colonization is widely believed to stimulate mineral nutrient uptake in plants, e.g., N, P, and K [ 16 ]. In this regard, AMF are effectively used to enhance the biological nitrogen fixation and phosphate solubilization processes in soil and the rhizosphere [ 75 ]. In addition, mycorrhizal inoculation significantly enhanced dehydrogenase activity, which could be attributed to the ability of AMF to improve the physical and chemical properties of soil, especially the soil structure, enhancing the organic matter decomposition and remobilizing nutrients, including nitrogen, in the rhizosphere and soil [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMF colonization is widely believed to stimulate mineral nutrient uptake in plants, e.g., N, P, and K [ 16 ]. In this regard, AMF are effectively used to enhance the biological nitrogen fixation and phosphate solubilization processes in soil and the rhizosphere [ 75 ]. In addition, mycorrhizal inoculation significantly enhanced dehydrogenase activity, which could be attributed to the ability of AMF to improve the physical and chemical properties of soil, especially the soil structure, enhancing the organic matter decomposition and remobilizing nutrients, including nitrogen, in the rhizosphere and soil [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using wheat plants under water deficit stress (each pot three times weekly irrigating, 25 ml per time), the effect of F. mosseae (AMF) was studied ( Moradi Tarnabi et al, 2020 ). The results showed that symbiotic association between plant and AMF and irrigation not only affect transcription profile of the plant growth, but also membrane components and cell wall.…”
Section: Beneficial Fungimentioning
confidence: 99%
“…The selected genes were associated to chitinase activity ( AY973229.1 ), cellulose biosynthetic process ( XM_020345004.1 ), and beta-glucosidase BoGH3B-like ( XM_020296045.1 ). Chitin-related genes such as chitinase detect chitin molecules of fungus as a signal to trigger a defense response an increase the plant tolerance ( Moradi Tarnabi et al, 2020 ). A stress-response related role can be considered for cellulose, since cellulose microfibrils and the other factor that lead the direction of cell growth can be regulated by water availability ( Wang T. et al, 2016 ).…”
Section: Beneficial Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different biofertilizers, arbuscular mycorrhizal fungi (AMF) is the most effective microbial symbioses for improving the growth and yield of the majority (90%) of plants, including flowering plants, bryophytes, and ferns [16][17][18]. Under the P deficiency in the soil, the AMF can influence plant community development, nutrient uptake, water relations, and above-ground productivity, and can also act as bio-protectants against pathogens and toxic stresses [12].…”
Section: Introductionmentioning
confidence: 99%